Strategies for Nurturing Talented and Achieving Students through the Got Talent Program - Rahmania, Nurani; Rohmah, Binti Nur (STAI Miftahul Ula Nganjuk, 2024)
This study aims to describe the implementation of talent and achievement development for students at MI Miftahul Huda through the Got Talent program. The research also identifies the supporting and inhibiting factors as well as the implications of this talent development program. The school’s student development efforts are conducted through extracurricular activities that promote holistic growth in alignment with national education objectives. The research method employed is qualitative, utilizing data collection techniques such as observation, interviews, and documentation. Data analysis followed the process of data collection, condensation, presentation, and conclusion drawing. The findings indicate that student development at MI Miftahul Huda is divided into academic and non-academic coaching. The Got Talent program is successfully implemented, as evidenced by the numerous championships won by students in various competitions. Additionally, the program encourages the development and well-being of talented students, in line with the Self-Determination Theory (SDT). Key supporting factors for the program include the motivation and support from parents and teachers, along with adequate facilities. However, inhibiting factors include students' lack of commitment during training, insufficient facilities for self-defense training, limited funds for large-scale events, and a lack of time for development activities.